Improving Local Community Public Services: Revealing Hurdles and Strategic Remedies - Wirahayu, Choif Puspa; Mursyidah, Lailul (Universitas Muhammadiyah Sidoarjo, 2023)
This research investigates the complexities within public service delivery at the Buduran Sub-District Office in Sidoarjo Regency, identifying issues arising from intricate procedures and demanding requirements. The study aims to uncover and analyze factors impacting the improvement of public service performance, employing a SWOT analysis to identify internal and external environmental factors. The strategic identification of five critical issues emerges, including inadequate infrastructure, public unfamiliarity with service procedures, limited service personnel, suboptimal workforce competencies, and administrative disorder at the village level. Corresponding strategic responses are proposed, such as infrastructure enhancement, intensified public education on service procedures, capacity building for civil servants, specialized recruitment in service areas, and fortified coordination with village administrations. The implications suggest targeted strategies for policymakers and public service administrators to address these challenges, thereby elevating service quality and responsiveness to societal needs. Highlights: SWOT Analysis: Identifying Internal and External Factors - Essential for strategic planning and understanding the landscape of service delivery challenges. Critical Issues in Service Delivery: Infrastructure, Public Awareness, and Human Resources - Addressing these facets is pivotal for enhancing service quality and efficacy. Strategic Responses: Infrastructure Development, Public Education, and Workforce Capacity Building - Implementing targeted strategies to address identified challenges and fortify service delivery mechanisms. Keywords: Public Service, Performance Improvement, Strategic Solutions, SWOT Analysis, Community Engagement